1989: From the Global Moment to its Regional and National Memories - Middell, Matthias (Comparativ, 2020)
The expectation expressed in 2009 that the many particular histories of 1989 would come together to form a great, coherent global history and that this would further deepen the interpretation established by the contemporaries witnessing a special moment in world history has not been fulfilled. Rather, different memories of 1989 are cultivated in different regions of the world, and most recent historiography is more concerned with the question of how the upheaval of 1989 in Eastern Europe is linked to the rise of populism. The article that introduces this thematic issue tries to offer some explanations for this development that can be seen as both an indicator and part of a departure from a certain ideology of globalization that has confused increasing connectivity worldwide with a neoliberal globalization project. Even if one limits oneself to the African continent, as most of the contributions in this issue do, it is already more than clear that this does not mean a withdrawal from global contexts and their memory, quite the contrary. In this respect, the reconstruction of some important moments of the African contribution to the global moment in 1989 is perhaps more illuminating for understanding this caesura than would be a further appropriation of the diversity of that year for a homogeneous narrative.